Tailoring the electrochemical performance of PEDOT:PSS via incorporation of spray dryer processed graphene oxide. (12th August 2022) - Karakoti, Manoj; Tatrari, Gaurav; Pandey, Sandeep; Dhapola, Pawan Singh; Jangra, Ritu; Mahendia, Suman; Pathak, Mayank; Dhali, Sunil; Singh, Pramod K.; Sahoo, Nanda Gopal
Summary: This work reports a comparative study of electrolytic behavior of PEDOT:PSS‐SPGO nanocomposite‐based supercapacitor devices in aqueous and polymer gel electrolytes. Initially, more purified and finely dispersed graphene oxide (SPGO) was synthesized by using a spray dryer process. Furthermore, PEDOT:PSS was mixed in a certain optimum concentration with SPGO and a PEDOT:PSS‐SPGO nanocomposite was prepared. The utility of PEDOT:PSS‐SPGO nanocomposite was investigated by fabricating its supercapacitor devices. Here, the incorporation of SPGO enhanced the electrochemical performance of the PEDOT:PSS by developing the PEDOT:PSS‐SPGO nanocomposite. The prepared nanocomposite‐based device exhibited the highest C sp of 134.66 and 155 F g −1 in polyvinyl alcohol‐phosphoric acid (PVA‐H3 PO4) )polymer gel and aqueous 1 M H3 PO4 electrolytes, respectively, at 5 mV s −1 which were higher than that of pure PEDOT:PSS and SPGO. In addition, this nanocomposite showed a good energy density and high‐power density of 10.79 W h kg −1 and 1529.29 W kg −1, respectively, in aqueous electrolyte. Abstract : Synthesis of PEDOT:PSS‐SPGO nanocomposite and its use for high performing supercapacitor device fabrications.